Acoustic signal investigation in the ice melting under high-power laser irradiation at a wavelength of 2940 nm. (June 2018) - Il'ichev, N.N.; Sidorin, A.V.; Gulyamova, E.S.; Pashinin, P.P.
Abstract: We have measured acoustic signals emerging in the melting of a thin (about 2 μm) ice layer, which is sandwiched between two substrates, under high-power laser irradiation at a wavelength of 2940 nm. A negative-pressure acoustic signal arising from the difference in the specific volumes of water and ice was found to occur in the ice melting. The amplitude of this signal was comparable to the amplitude of the positive-pressure signal produced under laser irradiation of the same layer of water. The shapes of acoustic signals were measured for different energy densities of the incident radiation. The variation of negative-pressure pulse shape with increasing radiation energy density was interpreted as a continuity break of the medium. The temperature and pressure in the layer were estimated in the heating of water and the melting of ice.